Phosphocreatine attenuates Gynura segetum-induced hepatocyte apoptosis via a SIRT3-SOD2-mitochondrial reactive oxygen species pathway - Li DP; Chen YL; Jiang HY; Chen Y; Zeng XQ; Xu LL; Ye Y; Ke CQ; Lin G; Wang JY; Gao H (Dove Medical Press, 2019)
Dong-Ping Li,1,* Ying-Ling Chen,1,* Hong-Yue Jiang,1,* Yun Chen,1 Xiao-Qing Zeng,1 Li-Li Xu,1 Yang Ye,2 Chang-Qiang Ke,2 Ge Lin,3 Ji-Yao Wang,1,4 Hong Gao1,41Department of Gastroenterology and Hepatology, Zhongshan Hospital, Fudan University, Shanghai, People’s Republic of China; 2State Key Laboratory of Drug Research & Natural Products Chemistry Department, Shanghai Institute of Materia Medica, Chinese Academy of Sciences, Pudong, People’s Republic of China; 3School of Biomedical Sciences, Faculty of Medicine, The Chinese University of Hong Kong, Hong Kong, Hong Kong SAR; 4Evidance-based Medicine Center of Fudan University, Shanghai, People’s Republic of China*These authors contributed equally to this work Purpose: To investigate the mitochondria-related mechanism of Gynura segetum (GS)-induced apoptosis and the protective effect of phosphocreatine (PCr), a mitochondrial respiration regulator.Methods: First, the mechanism was explored in human hepatocyte cell line. The mitochondrial oxidative stress was determined by fluorescence assay. The level of sirtuin 3 (SIRT3), acetylated superoxide dismutase 2 (Ac-SOD2), SOD2, and apoptosis were detected by Western blotting. Mito-TEMPO and cell lines of viral vector-mediated overexpression of SIRT3 and SIRT3H248Y, were used to further verify the mechanism of GS-induced apoptosis. GS-induced liver injury mice models were built by GS through intragastric administration and interfered by PCr through intraperitoneal injection. A total of 30 C57BL/6J mice were assigned to 5 groups and treated with either saline, PCr (100 mg/kg), GS (30 g/kg), or PCr (50 or 100 mg/kg)+GS (30 g/kg). Liver hematoxylin and eosin (HE) staining, immunohistochemical analysis, and blood biochemical evaluation were performed.Results: GS induced hepatocyte apoptosis and elevated levels of mitochondrial ROS in L-02 cells. The expression of SIRT3 was decreased. Downregulation of SIRT3 was associated with increased levels of Ac-SOD2, which is the inactivated enzymatic form of SOD2. Conversely, when overexpressing SIRT3 in GS-treated cells, SOD2 activity was restored, and mitochondrial ROS levels and hepatocyte apoptosis declined. Upon administration of PCr to GS-treated cells, they exhibited a significant upregulation of SIRT3 and were protected against apoptosis. In animal experiments, serum ALT level and mitochondrial ROS of the mice treated with GS and 50 mg/kg PCr were significantly attenuated compared with only GS treated. The changes in SIRT3 expression were also consistent with the in vitro results. In addition, immunohistochemical analysis of the mouse liver showed that Ac-SOD2 was decreased in the PCr and GS co-treated group compared with GS treated group.Conclusion: GS caused liver injury by dysregulating mitochondrial ROS generation via a SIRT3-SOD2 pathway. PCr is a potential agent to treat GS-induced liver injury by mitochondrial protection.Keywords: Gynura segetum, apoptosis, mitochondrial, ROS, SIRT3, phosphocreatine